SAT0540 Power Doppler Ultrasound Imaging of The Joint-Draining Lymph Node Complex in Rheumatoid Arthritis. (15th July 2016) - Manzo, A.; Benaglio, F.; Vitolo, B.; Bugatti, S.; Caporali, R.; Montecucco, C.
Abstract : Background: The afferent lymphatic network and the draining lymph node (LN) are fixed environments acting as remote complementary check-points through progressive phases of the inflammatory response. LN Power Doppler ultrasonography (PDUS) is a non-invasive and sensitive imaging technique commonly adopted in the preoperative diagnostic work-up of cancers. Whether the draining LN undergoes PDUS-sensitive dynamic modifications during chronic inflammation in humans and whether these modifications can be tracked to improve disease assessment is currently unclear. Objectives: To investigate axillary LN sono-morphology and Doppler activity in established RA, defining the existence of alterations compared to healthy individuals and dissecting their relationship with synovitis in peripheral joints. Methods: 40 RA patients refractory to conventional synthetic DMARDs (DAS28≥3.2) were evaluated through complete clinical and PDUS examination in hands/wrists and axillary LN. 20 healthy individuals served as controls. 31 patients starting anti-TNF treatment were followed-up prospectively with further assessments at weeks 4 and 24. Axillary LN PDUS characteristics were assessed according to 0–3 semi-quantitative scores for global LN volume, structure of the lymphocyte-rich cortex and local perfusion. Patient-related indices for each parameter were constructed for comparative, correlative, response-to-treatment and outcome analyses. Synovitis degree (PD and gray scale) was quantified according to 0–3 semi-quantitative scales and 12-joint cumulative indices. Results: Baseline assessment of perfusion and sono-morphologic characteristics showed the existence of quantitative changes in a subset of RA axillary LN, collectively leading to a distinct sonotype differentiating patients and controls. Combining data derived from morpho-structural and vascularity indices, evidence for parameters exceeding the threshold of controls was restricted to 17 out of 40 patients (42.5%), indicating variable levels of LN response despite established active disease. No relationships were observed between LN parameters and ACPA-RF status, DAS28, acute phase reactants, tender-swollen joint counts. Significant correlations (at systemic and ipsilateral level) were instead consistently detected when sensitive PDUS imaging of the synovium was applied (LN-joint PD index correlation: r=0.35, p=0.03). Plasticity of the observed LN alterations was confirmed by responsiveness analyses showing clear-cut reduction at week 24 of both structural and perfusion scores in patients with LN alterations at baseline (LN PD index: p<0.002, LN cortical index: p<0.02, LN volume index: p<0.03). Patient stratification according to EULAR response at 6 months demonstrated the existence of specific differences in baseline LN scores (but not in clinical features and joint US parameters) with significant decrease in the moderate/non responder group (LN PD index median [IQR] 0 [0–1] vs 2 [1–4.25], p=0.01). At its lowest detectable threshold, the LN perfusion index was the only negative predictor of achievement of good response (OR=0.08, p=0.005). Conclusions: PDUS assessment of axillary LN allows detection of inflammatory-related changes in a subset of patients with active established RA. Lack of signs of LN challenge appears a negative predictor of clinical response. Disclosure of Interest: None declared